Changes in Household Consumption Patterns After the Nutritious Eating Program in Kendari City - Ichsanuddin Akbar; Astil Harli Roslan (PT PUSTAKA CENDEKIA GROUP, 2024)
The Nutritious Eating Program (MBG) is a government policy that aims to improve the nutritional quality of the community, especially school-age children. In addition to having a direct impact on program recipients, MBG also has the potential to affect household consumption patterns indirectly. This study aims to analyze changes in household consumption patterns after the implementation of the Nutritious Eating Program (MBG) in Kendari City and identify the factors that influence these changes. This research uses a qualitative approach with a descriptive design. The research informants consisted of five people from households receiving the Nutritious Eating Program in Kendari City and were randomly selected. Data collection was carried out through in-depth interviews and simple observations, then analyzed using thematic analysis. The results of the study show that the implementation of the Nutritious Eating Program in Kendari City encourages an increase in the diversity and quality of household food consumption, especially in the consumption of vegetables, fruits, and protein side dishes, as well as reducing the consumption of instant food and unhealthy snacks. Changes in consumption patterns are influenced by the level of household income, the number of family members, parental nutritional knowledge, children's eating habits, and access to nutritious food in urban environments. This study concludes that the Nutritious Eating Program in Kendari City plays a role as a trigger for changes in household consumption patterns, but the sustainability of its impact requires the support of nutrition education and sustainable local food policies.